Analysis of the Development of Video-Based Economic Learning Media - I Gst. Ayu Diah Utari; Silvia Ekasari; Patrisia Senita; Zilfana Zilfana; Abdurohim Abdurohim (Edumaspul: Jurnal Pendidikan, 2023)
The purpose of this research is to analyze the development of video-based economic learning media. This research uses research and development research, using the analysis, design, development, implementation, and evaluation (ADDIE) development model. The subjects that will be used in this research are class X students at the Medan City Private High School, consisting of 30 students. The object of this research is video-based learning media for economics subject matter as a learning medium. Data analysis techniques are used to calculate a valid and practical scale of the products produced. The research results show that the development of video-based economic learning media consists of analyzing the curriculum, student needs, subject matter, and formulating objectives.